Human Resource Management Practices in Culinary MSME Performance: Praktik Manajemen Sumber Daya Manusia dalam Kinerja Usaha Mikro, Kecil, dan Menengah (UMKM) di Bidang Kuliner - Febrina Niken Estevania Panjaitan; Rifdah Abadiyah (Indonesian Journal of Law and Economics Review, 2025)
General Background Micro, Small, and Medium Enterprises play a strategic role in Indonesia’s economy, particularly in labor absorption and local economic development. Specific Background In the culinary sector, rapid growth of coffee shops has intensified competition, making human resource management a critical managerial function. Knowledge Gap Despite extensive studies on MSME performance, limited research explores contextual and informal HRM practices within thematic culinary MSMEs. Aims This study examines the role of human resource management in supporting employee performance and operational sustainability at Kedai Waleho Kopitiam, a thematic coffee shop in Sidoarjo. Results Using a qualitative descriptive approach through interviews, observation, and documentation, the findings show that informal HRM practices covering recruitment, training, motivation, performance evaluation, and workplace relations contribute to improved productivity, service quality, customer satisfaction, and work efficiency. Novelty This study highlights the application of humanistic and contextual HRM practices in a family-based culinary MSME setting. Implications The findings provide practical insights for MSME owners to manage human resources adaptively without complex formal systems while maintaining sustainable business performance. Keywords: Human Resource Management, MSME Performance, Culinary Business, Employee Productivity, Service Quality Key Findings Highlights: Informal HR practices support employee productivity and operational stability Humanistic management fosters positive service interactions with customers Contextual HR approaches suit small-scale culinary enterprises